(3JMdjd hJUeje GdfXe (B/s - (3GdUjQaj, eMeOs ((3GdGScfOQjI(B: s (3eDSSI MhQS GdOhdjI(B, s, 2005)
(3fXe GdeYdheGJ GdeMShHI, JMdjd fXe GdeYdheGJ, JUeje fXGe GdeYdheGJ JWHjb hGNJHGQ fXGe GdeYdheGJ(B.s
(3GdeQGLY U(B.215s
Keywords: (3JMdjd GdfXes; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s